Social media use and self-esteem as predictors of the risk of experimentation with e-cigarettes among university students in Malaysia: Resistance to peer influence as mediator. - Teh, Xin Rou; Tam, Jing Yi Evelyn; Yap, Xue Li (2023)
Electronic or e-cigarette usage has become increasingly widespread across all age demographics, with a particular surge among young adults. Nevertheless, there are scarce studies that investigate the possible factors linked to young adults use of e-cigarettes in Malaysia. Therefore, this present study aims to examine a pathway through which social media use (SMU) and self-esteem would influence the risk of experimentation with e cigarettes with Resistance to Peer Influence (RPI) as the mediator. A total of 143 participants aged 18-24 from higher institutions in Malaysia were recruited using the purposive sampling method. There are 35.7 % participants were males while 64.3% were females. Majority (82.5%) of them were Chinese, followed by Malay (9.8%), and Indian (7.7%). The survey included demographic questions and the instruments, Social Networking Usage Questionnaire, Rosenberg Self-Esteem Scale (RSES), Resistance to Peer Influence Questionnaire (RPIQ), and Susceptibility to Smoking. Based on the findings, SMU use was a significant and positive predictor of the risk of experimentation with e-cigarettes whereas self-esteem was not a significant predictor of the risk of experimentation with e-cigarettes. Also, RPI was a full mediator of the relationship between self-esteem and risk of experimentation. In conclusion, the findings of present study able to benefits Ministry of Higher Education (MoHE) Malaysia, mental health professional, and university counsellor as they can conduct programme or intervention regarding to the harms of e-cigarettes as well as methods to exit from e-cigarettes use. This can aid in hinder the prevalence of the risk of experimentation with e-cigarettes among university students.